Realisation of small molecule libraries based on frameworks distantly related to natural products. Issue 17 (12th April 2018) - Aimon, Anthony; Karageorgis, George; Masters, Jacob; Dow, Mark; Craven, Philip G. E.; Ohsten, Martin; Willaume, Anthony; Morgentin, Rémy; Ruiz-Llamas, Nicolas; Lemoine, Hugues; Kalliokoski, Tuomo; Eatherton, Andrew J.; et al.
Abstract : Design and synthesis of compound libraries with focused molecular properties, based on NP-like scaffolds. Abstract : The availability of high-quality screening compounds is of paramount importance for the discovery of innovative new medicines. Natural product (NP) frameworks can inspire the design of productive compound libraries. Here, we describe the design and synthesis of four compound libraries based on scaffolds that have broad NP-like features, but that are only distantly related to specific NPs. The optimisation of syntheses of the scaffolds using [5 + 2] cycloaddition chemistry is detailed, together with methods to yield exemplar decorated screening compounds. In each case, a library was nominated for production, leading to a total of >2900 screening compounds that augmented the Joint European Compound Library of the European Lead Factory.